Mechanical metallurgy - Dieter, George Ellwood (McGraw Hill series in materials science and engineering, 1988)
Examines the behaviour of materials under stress and their reaction to a variety of hostile environments. This book covers mechanical metallurgy, from an understanding of the continuum description of stress and strain, through crystalline and defect mechanisms of flow and fracture, and on to a consideration of major mechanical property tests.